The Effect of Co-Branding and Brand Equity Mcdonalds X BTS on Purchase Intention of BTS Meal Products - Ghina Zhafira Roscha; Angelia Angelia; Nathaniel Bintang Mahaputra (Universitas Negeri Makassar, 2022)
This study discusses the effect of co-branding and brand equity of the BTS Meal product which is the result of the collaboration of the McDonalds serving company with the famous music group BTS. BTS Meal has become a very popular product, especially in Indonesia through campaign activities carried out by ARMY as a fandom of BTS. BTS Meal has received various responses from consumers regarding the uniqueness of the product, especially in the packaging of the product. The method used in this research is library research, where the researcher uses sources based on the literature to discuss the effects caused by the BTS Meal co-branding product and the applied brand equity. The results and discussion in this study indicate that the influence of branding between the two companies before the implementation of co-branding greatly affects the popularity of BTS Meal products. Through digital marketing and campaigns carried out by ARMY, BTS Meal has become a best-selling product in the market. In addition, the popularity of this product is influenced by its brand equity by displaying the uniqueness of the packaging and the combination of the McDonalds and BTS logos. With the influence of the popularity of BTS Meal products and their brand equity, it affects the purchase intention of consumers to buy BTS Meal products based on the preferences made by ARMY on social media. The conclusion of this study shows that there is a very significant effect between co-branding and BTS Meal brand equity on consumers' purchase intentions.